Investigation of functional and sensory properties of plantain flour in citric acid - Ishiwu, Charles N.; Nnanwube, Ikechukwu A.; Nkem, Jasper O.; Ezegbe, Clement C. (Goodwood Publishing, 2023)
Purpose: This study investigated the effects of process variables on the proximate, functional, and sensory properties of plantain flour. Research Methodology: The plantain fruit was sorted and hand-peeled using kitchen knives. It was then cut into various slices of 2 – 6 mm and steeped in citric acid solutions with concentrations ranging between 1 – 5 %. The steeping time varied between 30 – 120 min. The pretreated plantain slices were processed into flours. Process parameters were analyzed using the response surface methodology of Design Expert software. Results: The proximate composition showed no significant differences (p > 0.05), but functional and sensory properties varied significantly (p < 0.05). Flour samples exhibited desirable bulk density, high water absorption capacity, and favorable swelling power, indicating potential for bakery and complementary foods. Sensory analysis revealed that citric acid pretreatment improved moldability, texture, and overall acceptability, with the best results at citric acid concentration of 2.79%, slice thickness of 5.63 mm, and steeping time of 50.41 minutes. Conclusions: Citric acid treatment significantly enhanced functional and sensory properties of plantain flour, making it suitable for diverse food applications Limitations: This study did not consider the application of other optimization methods, such as genetic algorithms and particle swarm optimization, to estimate the optimum points. Future studies could focus on these areas Contribution: The validation of the optimization processes showed success in the application of citric acid in the production of novel plantain flour.